(3YeOI GdeajO hYOI GdeLjO aj eYQaI daX GdJLhjOs - (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYGde GdebQi JdGhI GdbQBf dGJMSH GdJLhjO eOkG Ch Cf JSOO HYO eO geRI s
(3BNQgG (B:s
(3hGYde HCfc LGFQ ai XdegG Gf bSegG HGdbUjOI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
Keywords: (3GdbQGAGJ hGdJLhjOs